The dahliagram: An interdisciplinary tool for investigation, visualization, and communication of past human-environmental interaction - Frachetti, Michael; Di Cosmo, Nicola; Esper, Jan; Khalidi, Lamya; Mauelshagen, Franz; Oppenheimer, Clive; Rohland, Eleonora; Büntgen, Ulf (Science advances, 2023)
Investigation into the nexus of human-environmental behavior has seen increasing collaboration of archaeologists, historians, and paleo-scientists. However, many studies still lack interdisciplinarity and overlook incompatibilities in spatiotemporal scaling of environmental and societal data and their uncertainties. Here, we argue for a strengthened commitment to collaborative work and introduce the "dahliagram" as a tool to analyze and visualize quantitative and qualitative knowledge from diverse disciplinary sources and epistemological backgrounds. On the basis of regional cases of past human mobility in eastern Africa, Inner Eurasia, and the North Atlantic, we develop three dahliagrams that illustrate pull and push factors underlying key phases of population movement across different geographical scales and over contrasting periods of time since the end of the last Ice Age. Agnostic to analytical units, dahliagrams offer an effective tool for interdisciplinary investigation, visualization, and communication of complex human-environmental interactions at a diversity of spatiotemporal scales.
Keywords: výzkumný projekt; znalosti; Communication; Knowledge; lidé; Research Design; Humans; komunikace